Structural Behaviour Of Asymmetrically Designed Timber-Concrete Hybrid Buildings With Different Roof Materials Subjected To El Centro Earthquake Excitations - Mahmoud, Mostafa Ahmed Sayed Ahmed (Universiti Sains Malaysia, 2022)
Buildings are susceptible to earthquake disaster if the seismic loading is not considered in the design. Irregular buildings have been proven to perform badly during earthquake events. Due to lack of investigation on asymmetrical timber-concrete hybrid building under earthquake loading, a 1/4 scale of this type of building model was tested seismically using a unidirectional shake table. Six structural model frequencies varied by using diagonal wooden braces and steel cables were examined, which are 5.88 Hz, 4.55 Hz, 3.85 Hz, 3.33 Hz, 2.70 Hz, 2.50 Hz. Two different roof materials namely heavy metal roof and clay roof tile were considered for the building models with frequencies 3.85 Hz and 2.70 Hz. The model was subjected to El Centro ground motion excitation scaled to 0.08 g, 0.16 g, 0.24 g, 0.32 g resembling 25%, 50%, 75%, and 100% of the ground motion strength, respectively. Seven LVDTs and nine accelerometers were used to measure the seismic response of the model during the shake table test for displacement and acceleration, respectively. The change of roof material shows a clear effect on the seismic responses in terms of acceleration and relative displacement. Heavier roof material shows larger amplitudes across the maximum displacement time history, but a clear decrease in acceleration response for the roof level as compared with lighter roof material. Global deformation and acceleration amplification factors were obtained and evaluated. The relationships between the maximum roof displacement and PGA, and the maximum roof displacement and building frequency were established. The maximum displacement of the model is the highest when the natural building frequency is close to the predominant frequency of El Centro ground motion. A prediction equation for the maximum roof displacement relating the peak ground displacement and building frequency was then proposed.